HUBUNGAN INTRAVESICAL PROSTATIC PROTRUSION DENGAN Q MAX UROFLOWMETRI - Al-fath, Muhammad Fauzan; Sutapa, Hendra; Istiana, Istiana; Rahman, Eka Yudha; Panghiyangani, Roselina (Homeostasis, 2023)
Benign prostatic hyperplasia (BPH) is a benign tumor that is often found in men. IPP is a protrusion of the prostate starting from the neck of the bladder into the cavity of the bladder which results in a ball valve mechanism in the neck of the bladder thereby disrupting the flow of urine past the neck of the bladder. Uroflowmetry test is the simplest test to measuring the amount of urine that is urinated divided by the duration of micturition (ml/second). This research aims to analyze the relationship between IPP and q max of uroflowmetry measurements in BPH patients with LUTS at Ulin General Hospital, Banjarmasin. This research is analytic observational with cross sectional method. The research subjects were BPH patients at Ulin General Hospital, Banjarmasin who met the inclusion and exclusion criteria. The independent variable is Intravesical Prostatic Protrusion. The dependent variable is the results of the Uroflowmetry q max examination. Data analysis used Spearman's rank correlation test. The results showed that the average size of enlarged prostate was 8.623 ± 5.694 mm and the average q max uroflowmetry was 9.945 ± 4.238 ml/second. Conclusion In this study p = 0.029 indicating that there is an adequate correlation and has a negative relationship between Intravesical Prostatic Protrusion and q max uroflowmetry. The higher the Intravesical Prostatic Protrusion measurement, the lower the q max uroflowmetry.